Contractile-Ring Assembly in Fission Yeast Cytokinesis: Recent Advances and New Perspectives - Lee, I-Ju (Cytoskeleton (Hoboken), 2012)
The fission yeast Schizosaccharomyces pombe is an excellent model organism to study cytokinesis. Here, we review recent advances on contractile-ring assembly in fission yeast. First, we summarize the assembly of cytokinesis nodes, the precursors of a normal contractile ring. IQGAP Rng2 and myosin essential light chain Cdc4 are recruited by the anillin-like protein Mid1, followed by the addition of other cytokinesis node proteins. Mid1 localization on the plasma membrane is stabilized by interphase node proteins. Second, we discuss proteins and processes that contribute to the search, capture, pull, and release mechanism of contractile-ring assembly. Actin filaments nucleated by formin Cdc12, the motor activity of myosin-II, the stiffness of the actin network, and severing of actin filaments by cofilin all play essential roles in contractile-ring assembly. Finally, we discuss the Mid1-independent pathway for ring assembly, and the possible mechanisms underlying the ring maturation and constriction. Collectively, we provide an overview of the current understanding of contractile-ring assembly and uncover future directions in studying cytokinesis in fission yeast.